2004
DOI: 10.1111/j.1467-7687.2004.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant social attention predicts preschool social cognition

Abstract: Recent research examining infants' understanding of intentional action claims to be studying the early origins or precursors of children's later theories of mind If these infant understandings are continuous with later preschool achievements, there should be empirical connections between the two. We provide initial evidence that infants' social attention predicts later social cognition. Specifically, 14-month-olds' habituation to human intentional action significantly predicts later preschool mentalistic const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 48 publications
13
110
4
5
Order By: Relevance
“…Children are already able to understand others' intention in the beginning of their second year of life, even if this does not mean they have a fully fledged adult level of intention-understanding. In any event, the early understanding of intention as well as joint attention are related to the later development of a theory of mind (Charman et al, 2000;Olineck & Poulin-Dubois, 2005;Wellman, Phillips, Dunphy-Lelii, & LaLonde, 2004). In particular, Colonnesi, Rieffe, Koops, and Perucchini (2007), in a study related to the present study, found that the ability to follow the pointing gesture at 12 months of age predicts the later ability to explain others' behaviour in a psychological way and the perception understanding at the age of three years.…”
Section: Discussionmentioning
confidence: 92%
“…Children are already able to understand others' intention in the beginning of their second year of life, even if this does not mean they have a fully fledged adult level of intention-understanding. In any event, the early understanding of intention as well as joint attention are related to the later development of a theory of mind (Charman et al, 2000;Olineck & Poulin-Dubois, 2005;Wellman, Phillips, Dunphy-Lelii, & LaLonde, 2004). In particular, Colonnesi, Rieffe, Koops, and Perucchini (2007), in a study related to the present study, found that the ability to follow the pointing gesture at 12 months of age predicts the later ability to explain others' behaviour in a psychological way and the perception understanding at the age of three years.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence in favor of this final prediction comes from several recent longitudinal studies documenting that infants' action analysis predicts their responses, some years later, on verbal theory of mind measures (Aschersleben & Hohenberger, 2007;Kuhlmeier & Yamaguchi, 2007;Poulin-Dubois & Olineck, 2007;Wellman, Phillips, Dunphy-Lelii, & Lalonde, 2004). Infants who respond more systematically to the intentional structure of others' actions go on to become preschoolers who respond more systematically on classic theory of mind assessments, like the false-belief task.…”
Section: Resultsmentioning
confidence: 99%
“…Essa mudança cultural pode reverter em uma melhor qualidade da interação entre pais e filhos, favorecendo o desenvolvimento infantil (Bolsoni-Silva & Del Prette, 2002;Overstreet et al, 2005;Willman, Phillips, Dunphy-Lelli & Lanlonde, 2004 …”
Section: Discussionunclassified